Pedagogical friendships between teachers and students in one-to-one tuition : An interview study on the meanings in the learning process - Flores i Mula, Miquel (Taideyliopiston Sibelius-Akatemia, 2025)
This study examines pedagogical friendships in one-to-one instrumental tuition within higher music education, exploring their impact on students' learning processes. Through qualitative research, four students who experienced friendships with their teachers during their bachelor’s studies were interviewed through semi-structured interviews. Findings reveal that teacher-student friendships generally create a positive learning atmosphere, fostering emotional support and trust. Students reported that closeness in the relationships improved communication and enhanced their confidence in lessons. However, ethical concerns were exposed, including fairness among classmates, objectiveevaluation, and personal boundaries. While the students’ viewed these friendships as beneficial, they also mentioned that personal connections influenced the learning environment in different ways. The study is based in the duality that pedagogical friendships have. They can enhance emotional well-being and learning process development, but only if there is ethical awareness. The findings contribute to discuss on several aspects of teacher-student relationships and friendships in music education, and the research suggest some recommendations on building an ethical and supportive teacher-student relationship.
Keywords: teacher-student-friendship; teacher-student-relationship; emotions; ethics; learning process; teacher-pupil relationship; fi=puhaltimet|sv=blåsinstrument|en=Wind Instruments|